Love Language Communication as an Effort to Strengthen the Character of Santri at Perguruan Diniyyah Puteri Padang Panjang - Tika, Diana Sartika; Wedra, Wedra Aprison; Sulasmi, Sulasmi (IJER (Indonesian Journal of Educational Research), 2024)
Character is a reflection of one's personal self, which is seen in aspects of daily attitudes and behavior. Diniyyah Puteri College students are expected to have the following characteristics: worship experts and akhlakul karimah, strong mujahid Allah, Intelligent as Khalifah. To understand the characteristics of the santri that have been determined, it is necessary to observe how teachers use communication. This study used the field observation method to observe how teachers communicate with students. From the results of observations made with students and teachers, it was found that to communicate with students, teachers at the Diniyyah Puteri College were not allowed to use communication that contained elements of communication viruses, such as commanding, blaming, belittling, comparing, labelling, threatening, advising, lying, entertaining, criticizing, insinuating, analyzing, and prying. To overcome this, teachers in instilling character values in santri must use seven languages of love for children consisting of positive words, comfortable body language, dive into feelings, want to listen, convey the contents of the heart, direct independence, and build cooperation.